The Role of the Syarhil Qur'an Branch in the Implementation of Dai Cadre Development - Kahfi, Al; Dzulhasnan , Ainul Haninah; Mohamoud, Mohamed Esse; Qonitah, Mona (STAI Publisistik Thawalib Jakarta, 2025)
Musabaqah Tilawatil Qur’an (MTQ) is a strategic platform for youth development. However, the Syarhil Qur’an branch remains under-researched regarding its role in enhancing da’wah capacity among young people. This study aims to analyze the strategic role of Syarhil Qur’an in shaping young preachers grounded in Qur’anic values. Using a qualitative and phenomenological approach, data were collected through interviews, observations, and documentation. The findings indicate that the strategic role of Syarhil Qur’an in youth preacher development lies in its ability to integrate Qur’anic text mastery, thematic interpretation, and rhetorical skills in delivering contextual and relevant da’wah messages. The training process is carried out systematically through teamwork, in-depth understanding of verses, public speaking exercises, and the formation of Qur’anic leadership and spiritual character. The positive impact of Syarhil Qur’an optimization is reflected in increased self-confidence, critical thinking skills, and adaptability to social issues and digital developments. Recommendations for developing Syarhil Qur’an include curriculum reform based on contemporary issues, integrating digital media in training, enhancing trainer professionalism, and forming alumni communities as part of a sustainable da’wah ecosystem. Syarhil Qur’an cultivates young Qur’anic preachers who are communicative, critical, contextual, and prepared to face the challenges of modern da’wah.